The pedagogy of discomfort - Lisa Elzey Mercer; Deana McDonagh, Ph.D. (Discern, 2021)
Education is meant to be a transformative experience. In the practice of transformative pedagogy, instructors provide students with the time and space to explore their own set of beliefs, values, and standards and how they incorporate those beliefs into their work, subconsciously and consciously. At times transformative pedagogy can be uncomfortable, however, the value of discomfort in the pedagogical process of a design course is the ability to acknowledge a gap of knowledge in our social experiences and then learn from that gap of knowledge. This paper will focus on the value of transformative pedagogy in working through discomfort when learning about limit-situations, developing a foundation for transformative pedagogy in a course setting, the importance of critical thinking in transformative pedagogy, and how transformative pedagogy is presented when the focus is on ethics, disability, and responsible design. By embedding ethics, critical consciousness, and strategic thinking, the process translates into a transformative practice of design and innovation. Students learn new ways of affecting change with a multiplicity of ideas when educators engage in transformative pedagogy. It is also to ascertain what kind of learning enables people to create solutions for communities involved in a continuously ongoing process of defining sustainable development.